In situ transcriptomic and metabolomic study of the loss of photosynthesis in the leaves of mixotrophic plants exploiting fungi. (18th March 2019) - Lallemand, Félix; Martin‐Magniette, Marie‐Laure; Gilard, Françoise; Gakière, Bertrand; Launay‐Avon, Alexandra; Delannoy, Étienne; Selosse, Marc‐André
Summary: Mycoheterotrophic plants have lost photosynthesis and obtain carbon through mycorrhizal fungi colonizing their roots. They are likely to have evolved from mixotrophic ancestors, which rely on both photosynthesis and fungal carbon for their development. Whereas our understanding of the ecological and genomic changes associated with the evolutionary shift to mycoheterotrophy is deepening, little information is known about the specific metabolic and physiological features driving this evolution. We investigated this issue in naturally occurring achlorophyllous variants of temperate mixotrophic orchids. We carried out an integrated transcriptomic and metabolomic analysis of the response to achlorophylly in the leaves of three mixotrophic species sampled in natura . Achlorophyllous leaves showed major impairment of their photosynthetic and mineral nutrition functions, strong accumulation of free amino acids, overexpression of enzymes and transporters related to sugars, amino acids and fatty acid catabolism, as well as induction of some autophagy‐related and biotic stress genes. Such changes were reminiscent of these reported for variegated leaves and appeared to be symptomatic of a carbon starvation response. Rather than decisive metabolic innovations, we suggest that the evolution towards mycoheterotrophy in orchids is more likely to be reliant on the versatility of plant metabolism and an ability to exploit fungal organic resources, especially amino acids, to replace missing photosynthates. Significance Statement: Some orchids have developed a heterotrophic lifestyle by obtaining carbon from mycorrhizal fungi, but the specific physiological features of this nutrition remain largely unknown. By investigating in situ metabolic and gene expression changes in achlorophyllous mutants of photosynthetic orchids, we showed that their survival does not rely on any major metabolic innovation but on an unusual mycorrhizal interaction that probably allows evolution towards full heterotrophy.